Constructing Ethical Critical Thinking at Pesantren - Muhamad Yasin; Muhammad Nabil Khasbulloh (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
Santri has been viewed as students who respect their kiai (teacher), parents and senior teachers, and might not able to think critically. The research aims to investigate efforts to foster students’ ethical critical thinking at pesantren (Islamic boarding school) in Kediri, East Java. This study uses a qualitative approach and sociological-phenemonological methods. Data obtained through observation and interviews. The research findings show that the patron-client pattern a pattern of relations between kiai and santri at pesantren can have both positive and negative impacts. The positive impact can be seen from the form of good relations and mutual respect between the kiai and students. Meanwhile, the negative impact refers to students’ fatalistic attitude towards life and an uncritical scientific view. Critical education in pesantren has practically been implemented even though partially. Education in pesantren is currently required to build an integrative educational paradigm by involving all human potential in fostering a critical, creative and democratic culture in addition to upholding ethics.